Drevesne naravne vrednote v registru naravnih vrednot Slovenije - Adamič, Pia Caroline (Acta silvae et ligni, 2020)
The aim of the study was a detailed analysis of the register of tree natural values of Slovenia with a total number of 2529 trees and groups of trees. In our research we presented the percentage of each tree species, its origin, criteria for evaluation, average and maximum dimensions for each tree species, the location of trees and tree damage. The locations of tree natural values were identified by coordinates and displayed on a map using ArcMap. We found that the most common tree species is Tilia platyphyllos (42.67 % of all trees) and that 87.4 % of the trees in the register belong to native species. Most of the non-native species come from North America, while most of the non-native trees come from Europe. The most important criterion is the size of the tree, especially its girth and height. The thickest tree in the register is the Gašper chestnut (1104 cm) and the tallest is the Sgerm spruce (62 m). Most exceptional trees are found near farms (31.2 %) and sacral objects (17.9 %). In the register, 36.3 % of the trees are healthy, 4.1 % have no data and the remaining 59.6 % are damaged. The map of tree natural value locations shows that tree densities are highest near Ljubljana and in Pohorje. The register contains a large amount of obsolete data, so an updated overview of the current state of tree natural values, which can be supplemented by new exceptional trees, should be prepared.
Keywords: drevesna dediščina; drevesne naravne vrednote; exceptional trees; heritage trees; izjemna drevesa; register naravnih vrednot Slovenije; register of natural values of Slovenia; tree natural values